DEVELOPMENT AND VALIDATION OF A STANDARDIZED TOOL FOR ASSESSING THE MEDHO SARA (EXCELLENCE OF ADIPOSE TISSUE) WITH SPECIAL CONSIDERATION TO SNIGDHATA (UNCTUOUSNESS) EVALUATION. - SUMITH KUMAR M; PRADEEP GRAMPUROHIT; SUNIL S. JALALPURE; SHWETA PUJARI (The Bioscan, 2024)
This study aimed to create a uniform assessment methodology for evaluating the Medho Sara (excellent level of adipose tissue), specifically emphasising analysing Snigdhata (unctuousness). Medho Sara is one of the eight types of Sara described in the Ayurveda, and Snigdhata is a subjective factor that enhances the overall quality of adipose tissue. The study utilised a crosssectional survey approach to evaluate the correlation between Medho Sara norms and body fat percentage. A cohort of 253 individuals were enrolled, and their physical attributes, vocal parameters, and body fat percentage were assessed. The findings indicated that most of the subjects fell into the Madhyama Sara category, and there was a notable association between Snigdha Oshta, Snigdha Purisha, Bruhat Shareera and body fat percentage. The study emphasises the significance of Snigdhata in assessing Medho Sara and its correlation with body fat percentage. The results indicate that a sufficient quantity of adipose tissue is essential for specific physiological processes, such as enhancing the shine and appearance of hair, lips, and nails. The study highlights the importance of having a uniform instrument to evaluate Medho Sara, as it is crucial for the diagnosis and treatment of different health issues.